Classification of ComputerAssisted Canvas Analysis Methods in the Ontology on Attribution and Restoration of Paintings - D. M. Murashov; V. N. Beloozerov (Informaciâ i Innovacii)
Classifications of methods for analyzing the structure of painting canvas, and fabrics in the textile industry are constructed within the framework of the ontology for the subject area of attribution and restoration of paintings. The limited variety of practically applied methods in painting by x-ray analysis, and the perspective of the method of analyzing the texture of the canvas in reflected rays under directed lighting are noted.